1997
DOI: 10.1111/j.1532-5415.1997.tb01512.x
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Parkinson's Disease on Society, Family, and the Individual

Abstract: The direct costs of the disease reflect a small portion of the burden. The hidden costs, in the form of lost wages, informal care, and changing roles are substantial. Their magnitude is even more important when we consider that the family generally lives on a fixed income, and the caregiver is an older aged spouse. Medical practitioners will best be able to intervene if they look holistically at the patient with this disease. When treating symptoms themselves, practitioners need to be aware of the high level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
159
2
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(176 citation statements)
references
References 12 publications
8
159
2
7
Order By: Relevance
“…This can lead to poor psychosocial outcomes including reduced quality of life (QoL), emotional and financial strain, fatigue, sleep disturbances, social isolation and an increased risk of neuropsychiatric symptoms and chronic illness [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to poor psychosocial outcomes including reduced quality of life (QoL), emotional and financial strain, fatigue, sleep disturbances, social isolation and an increased risk of neuropsychiatric symptoms and chronic illness [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Early-onset PD may be a risk factor for depression [27] while research regarding the relationship between PD severity and depression has yielded mixed results [27,28,29]. Depression in PD (dPD) may precede the onset of motor symptoms [30], is often under-detected by medical professionals [31], and warrants significant attention from clinicians as it is related to a faster progression of physical symptoms, greater cognitive decline, poorer quality of life, increased caregiver burden, and decreased ability to care for oneself [32,33,34,35,36].…”
Section: Depression and Parkinson's Diseasementioning
confidence: 99%
“…5 PD is recognized for its high disease burden for the individual, in addition to its significant economic and social costs. 6 In Australia, it had a per annum direct financial cost of greater than AUD 775 million in 2011 and an average lifetime financial cost of AUD 144,000 per person, similar to the lifetime cost of cancer. 7 This is comparable to a number of European countries, where it has been reported that the mean cost ranged from EUR 2620 to EUR 9820 per patient over 6 months.…”
Section: Introductionmentioning
confidence: 99%